Energetic analysis of a thermal building using geothermal and solar energy sources. (December 2020) - Palmero-Marrero, Ana I.; Gomes, Filipa; Sousa, João; Oliveira, Armando C.
Abstract: The building sector is growing at a rapid pace and has become the third largest consumer of fossil energy, after industry and transportation. To achieve a significant reduction in building energy consumption, aiming a sustainable development, passive methods are not enough: renewable energy technologies should be integrated with passive building concepts and systems, in order to improve energy efficiency. Renewable energy sources (RES) have been largely deployed as green energy producers, reducing power consumption while minimizing greenhouse emissions — they are derived from natural processes that are continuously replenished. This study provides a case study of the implementation of this type of energy resources, in this case geothermal and solar energy sources, in an existing thermal building located in the interior of Portugal, using renewable technologies to satisfy electrical and thermal energy loads. Through dynamic thermal simulation, using the TRACE 700 software, it was possible to obtain results very close to measured ones, and also to assess the implementation of appropriate rationalization measures to reduce energy consumption and increase building energy efficiency.